Activation of AMPK in human fetal membranes alleviates infection-induced expression of pro-inflammatory and pro-labour mediators. Issue 4 (April 2015) - Lim, R.; Barker, G.; Lappas, M.
Abstract Introduction In non-gestational tissues, the activation of adenosine monophosphate (AMP)-activated kinase (AMPK) is associated with potent anti-inflammatory actions. Infection and/or inflammation, by stimulating pro-inflammatory cytokines and matrix metalloproteinase (MMP)-9, play a central role in the rupture of fetal membranes. However, no studies have examined the role of AMPK in human labour. Methods Fetal membranes, from term and preterm, were obtained from non-labouring and labouring women, and after preterm pre-labour rupture of membranes (PPROM). AMPK activity was assessed by Western blotting of phosphorylated AMPK expression. To determine the effect of AMPK activators on pro-inflammatory cytokines, fetal membranes were pre-treated with AMPK activators then stimulated with bacterial products LPS and flagellin or viral dsDNA analogue poly(I:C). Primary amnion cells were used to determine the effect of AMPK activators on IL-1β-stimulated MMP-9 expression. Results AMPK activity was decreased with term labour. There was no effect of preterm labour. AMPK activity was also decreased in preterm fetal membranes, in the absence of labour, with PROM compared to intact membranes. AMPK activators AICAR, phenformin and A769662 significantly decreased IL-6 and IL-8 stimulated by LPS, flagellin and poly(I:C). Primary amnion cells treated with AMPK activators significantly decreased IL-1β-induced MMP-9 expression. Discussion The decrease in AMPK activity in fetal membranes after spontaneous term labour and PPROM indicates an anti-inflammatory role for AMPK in human labour and delivery. The use of AMPK activators as possible therapeutics for threatened preterm labour would be an exciting future avenue of research.